"Code Red"—Recent IPCC Report Warns Time is Running Out on Climate Change. (7th September 2021) - Cartwright, Echo D.
Abstract : Imagine a world in which the sky is consistently imbued with an orange smoky haze. A simple walk to the mailbox or to retrieve the morning paper brings a burning sensation deep in your chest, burning eyes and coughing until you get back indoors. Outdoor activities such as jogging, or hiking become less frequent and weather determined, and sports events are only able to be held indoors in a controlled environment due to poor air quality. Thousands of communities are being ravaged resulting from repeated wildfires, floods, earthquakes, and destructive winds. Windows are constantly shut to keep outside air from coming in. If you're fortunate enough to have air conditioning you are able to stay cool against dangerous heat waves—those without such options suffer with degrading lung, heart and other life‐threatening diseases amidst the smoke and increasingly intense heat.